Pelvic Floor Reconstruction After Radical Prostatectomy: A Systematic Review and Meta-analysis of Different Surgical Techniques - Jianfeng Cui (Nature Portfolio, 2017)
Abstract Radical prostatectomy (RP) is the gold standard for the treatment of localized PCa. A meta-analysis was conducted to evaluate the effect of different techniques of pelvic floor reconstruction on urinary continence. A comprehensive search was made for trials that evaluated the efficacy of pelvic floor reconstruction. Relevant databases included PubMed, Embase, Cochrane, Ovid, Web of Science databases and relevant trials from the references. Random-effects model was used to estimate risk ratios (RRs) statistics. Pooled results of patients treated with posterior reconstruction (PR) demonstrated complete urinary continence improved at 1–4, 28–42, 90, 180 and 360 days following catheter removal. Anterior suspension (AS) was associated with improvement only at 28–42 days. The anterior reconstruction (AR) + PR was associated with urinary continence at 1–4, 90 and 180 days. AS + PR was not associated with any benefit. And PR improved social urinary continence at 7–14 and 28–42 days. No benefit was associated with AS. AR + PR had better outcomes at 90 and 180 days. AS + PR was significant improved at 28–42 and 90 days. Patients who underwent RP and PR had the least urinary incontinence. No significant benefit was observed after AS. AR + PR and AS + PR had little benefit in the post-operative period.